Inverse association of a traditional Korean diet composed of a multigrain rice-containing meal with fruits and nuts with metabolic syndrome risk: The KoGES - Kim, Min Jung; Hur, Haeng Jeon; Jang, Dai Ja; Kim, Myung-Sunny; Park, Sunmin; Yang, Hye Jeong (Frontiers in Nutrition, 2022)
Background Hansik, a traditional Korean diet, may have a beneficial impact on metabolic syndrome (MetS) risk as dietary westernization increases its prevalence. We examined the hypothesis that adherence to the hansik diet may be inversely associated with the risk of MetS and its components and sought to understand the gender differences in 58,701 men and women aged over 40. Materials and methods Hansik was defined using 14 components from which the Korean dietary pattern index (Kdiet-index) was generated by summing their scores. Low-hansik intake was defined as the Kdiet-index with <8. MetS was categorized based on the 2005 revised NCEP-ATP III criteria modified for Asians. Results The Kdiet-index score was negatively associated with the dietary inflammation index and showed that the high intake of a meal with multigrain rice, fruits, and their products, and nuts, and low intake of fried foods were inversely associated with MetS by 0.707, 0.864, 0.769, and 0.918 times, respectively, after adjusting for covariates. More women and participants with more educated and lower income belonged to the high-hansik group, and participants with high self-rated health scores consumed more hansik. All participants on a high-hansik diet were associated with a 0.87 time lower risk of MetS. Specifically, the association between hansik intake and MetS risk was not significant among men following stratification by gender. Body composition, including the body mass index, waist circumference, and fat mass, was inversely associated with hansik intake, while the skeletal muscle mass index was positively associated with the hansik intake in each gender and all participants. In all the participants in the high-hansik group, no significant changes were seen in the serum glucose and HDL concentration. However, a high-hansik intake showed lower blood pressure and serum LDL and triglyceride concentrations only in men and a higher glomerular filtration rate in both genders. Conclusions Hansik intake might improve MetS risk, with its primary beneficial effects on body composition, dyslipidemia, and blood pressure gender-dependently.